Evidence to support phytosanitary policies–the minimum effective heat treatment parameters for pathogens associated with forest products - Noseworthy, Meghan K.; Allen, Eric A.; Dale, Angela L.; Leal, Isabel; John, Esme P.; Souque, Tyranna J.; Tanney, Joey B.; Uzunovic, Adnan (Frontiers in Forests and Global Change, 2024)
Research on reducing the movement of pests on wood products has led to several options for safer trade including heat treatment of wood to mitigate pests. In this study, pathogenic organisms commonly regulated in the trade of forest products were tested to determine the minimum heat dose (temperature and time) required to cause mortality. The mycelial stage of tree pathogens, Heterobasidion occidentale, Grosmannia clavigera, Bretziella fagacearum, Phytophthora cinnamomi, P. lateralis, P. ramorum and P.xmultiformis, which may be found in wood products, were tested in vitro using the Humble water bathwith parameters simulating the rate of heat applied to wood in a commercial kiln. The lethal temperature for the pathogens ranged from 44-50 °C for a 30-minute treatment duration. A molecular diagnostic method to confirm pathogen mortality was available for five of the species heat treated. RNA detection using reverse transcription real-time PCR was used to validate pathogen mortality following treatment for: P. ramorum, P. lateralis, P. cinnamomi, P. x multiformis and G. clavigeraPathogen mortality was confirmed with RNA detection using reverse transcription real-time PCR for a subset of Phytophthora spp. and G. clavigera samples.